Optimisasi Economic Dispatch dengan Transmission Loss Menggunakan Metode Extended Lagrange Multiplier dan Gaussian Particle Swarm Optimization (Gpso) - Komsiyah, Siti (ComTech: Computer, Mathematics and Engineering Applications, 2014)
In the operating process of electrical energy, economic planning is the main goal to be achieved. The goal of economic dispatch problem is determining the combination of optimal power distribution to a number of operating generator units so that the electricity demand in a certain area is fulfilled without ignoring the constraints that exist, so it is obtained a minimum total generation cost. Optimization method that is used is the Gaussian Particle Swarm Optimization (GPSO), while for the validation of the results, the obtained solution with the GPSO will be compared with the solution obtained by mathematical methods Extended Lagrange Multiplier (ELM) or the Lagrange multiplier method which its functions are expanded. The solution that is calculated is generation output in Megawatt of 23 thermal generating units system in Mahakam, East Kalimantan, which had a total cost of optimal generating (minimum).